Diseño de un esterilizador industrial por concentración de energía solar, para alimentos enlatados (2014)
This paper presents the design of a solar thermal collector, to be implemented in a steam autoclave in an industrial sterilization process of canned food, for Bogotá city, Colombia. The type of solar collector is based on weather and solar radiation parameters of the area, choosing the vacuum tube collector with heat pipe. To validate the design, a finite element analysis carried out in a single solar collector tube, focused on the analysis of the process temperatures required, taking account the incident radiation of the study area in the day of larger distance between the Sun and Earth.